Estimation of Understorey Carbon Stocks in Post-Mining Land: A Case Study of One-Year Revegetation at PT Insani Baraperkasa Site Loa Janan, East Kalimantan - Kiamah Fathirizki Agsa Kamarati; Agus Wiramsya Oscar; Pandhu Rochman Suosa Putra; Adnan Putra Pratama; Christine Elia Benedicta; Adelia Juli Kardika (JURNAL AGRIMENT, 2025)
Post-mining land rehabilitation is an important strategy to mitigate climate change and conserve tropical ecosystems. Surface mining activities in East Kalimantan have caused ecological degradation and the release of carbon stored in vegetation and soils. Revegetation has been widely practiced as the main approach to restore ecosystem functions, including initial carbon accumulation by understory plants. This study aims to estimate the carbon stock of the understory on post-mining land that has undergone revegetation for one year at the PT Insani Baraperkasa site in Loa Janan, East Kalimantan. The method used was destructive sampling of understory biomass from 10 plots measuring 5 m x 5 m, each with subplots measuring 0.5 m x 0.5 m. Biomass samples were dried and converted to carbon. The results showed an average carbon stock of 1.26 tons/ha. These results suggest that understorey vegetation plays an important role in early stage carbon recovery on post-mining land. Understory carbon monitoring can be an effective early indicator to measure the success of ecosystem restoration. Keywords: revegetation, understorey, post-mining, carbon